Thermal Stability and Flame Resistance of the Coextruded Wood-Plastic Composites Containing Talc-Filled Plastic Shells - Runzhou Huang; Xian Zhang; Zhilin Chen; Minli Wan; Qinglin Wu (International Journal of Polymer Science)
Talc is a popular filler for the fabrication of plastic composites. The presence of talc helps improve mechanical, thermal, and flame resistance properties of the composite. In this work, we report the influence of a talc-filled plastic shell layer on thermal stability and fire flammability of the core-shell structured wood high-density polyethylene (HDPE) composites manufactured through coextrusion. The result showed that morphological analysis of the char layer after combustion confirmed the formation of a continuous surface char layer with talc addition in the composites, helping block fire penetration and enhance overall fire resistance of the composites. The shell thickness averaged at 1.0±0.2 mm, which represents a fair thick shell over a 10 mm thick WPC core layer. The surface of regular wood-filled HDPE showed large cracks, allowing more rapid fire penetration and reducing its fire resistance. At 800°C, average residual weight for all composite was 21.5±13.8%, most of which was attributed to the inorganic nonvolatile talc components. With the increase of talc level, THR values of coextruded WPC decreased from 302.47 MJ/m2 (5 wt% of talc) to 262.96 kW/m2 (50 wt% of talc). When talc content in the shell layer was less than 25 wt%, the flame resistance properties were slightly enhanced compared with the composites containing unmodified HDPE shells. When talc content in the shell exceeded 25 wt%, the composite’s total heat release and its rate substantially decreased.